2015
DOI: 10.1002/adma.201501838
|View full text |Cite
|
Sign up to set email alerts
|

All Metal Nitrides Solid‐State Asymmetric Supercapacitors

Abstract: Two metal nitrides, TiN porous layers and Fe2 N nanoparticles, are grown uniformly with the assistance of atomic layer deposition on vertically aligned graphene nanosheets and used as the cathode and anode for solid-state supercapacitors, respectively. Full cells are constructed and show good flexibility, high-rate capability, and 98% capacitance retention after 20,000 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
192
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(202 citation statements)
references
References 57 publications
9
192
1
Order By: Relevance
“…In order to improve the rate capability of NiCo2O4 electrodes, we introduced titanium nitride (TiN) to form NiCo2O4@TiN core-shell nanostructures with NiCo2O4. TiN attracted our attention due to the following reasons: 1) TiN is already commonly used in industry for electronics and wear resistance applications due to its low cost, scalability, and superior corrosion resistance [46,47]; 2) as a metallic material, TiN offers superb electrical conductivity (4000-55500 S cm -1 ) and mechanical stability [48][49][50]; 3) previous reports have demonstrated that transition metal nitrides are capable of delivering high energy and power density as supercapacitor electrodes [51,52]. Meanwhile, by employing atomic layer deposition (ALD), we were able to conformally grow a TiN shell onto complex nanostructures such as the NiCo2O4 nanofiber arrays without altering the desired structural features of the underlying NiCo2O4 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the rate capability of NiCo2O4 electrodes, we introduced titanium nitride (TiN) to form NiCo2O4@TiN core-shell nanostructures with NiCo2O4. TiN attracted our attention due to the following reasons: 1) TiN is already commonly used in industry for electronics and wear resistance applications due to its low cost, scalability, and superior corrosion resistance [46,47]; 2) as a metallic material, TiN offers superb electrical conductivity (4000-55500 S cm -1 ) and mechanical stability [48][49][50]; 3) previous reports have demonstrated that transition metal nitrides are capable of delivering high energy and power density as supercapacitor electrodes [51,52]. Meanwhile, by employing atomic layer deposition (ALD), we were able to conformally grow a TiN shell onto complex nanostructures such as the NiCo2O4 nanofiber arrays without altering the desired structural features of the underlying NiCo2O4 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric and hybrid supercapacitors (HSCs) have been extensively studied as a promising strategy to increase the energy density20212223242526. A typical HSC consists of both faradaic and capacitive electrodes1227.…”
mentioning
confidence: 99%
“…36 In view of these studies and other recent work using TiN as the shell in core-shell supercapacitor structures, [37][38][39] there is a signicant need to understand how the formation of surface oxide affects the electrochemical behaviour of TiN surfaces. Herein we have applied various oxidation treatments to low area titanium nitride surfaces and linked their charge storage capacity to a detailed characterisation of the electrode surfaces.…”
mentioning
confidence: 99%